Effects of low seawater pH on the marine polychaete Platynereis dumerilii - Wäge, Janine; Larsson, Tomas; Simakov, Oleg; Arendt, Detlev (Marine pollution bulletin, 2015)
An important priority for any organism is to maintain internal cellular homeostasis including acid-base balance. Yet, the molecular level impacts of changing environmental conditions, such as low pH, remain uncharacterised. Herein, we isolate partial Na+/H+ exchangers (NHE), carbonic anhydrase (CA), and calmodulin (CaM) genes from a polychaete, Platynereis dumerilii and investigate their relative expression in acidified seawater conditions. mRNA expression of NHE was significantly down-regulated after 1h and up-regulated after 7days under low pH treatment (pH 7.8), indicating changes in acid-base transport. Furthermore, the localisation of NHE expression was also altered. A trend of down regulation in CA after 1h was also observed, suggesting a shift in the CO2 and HCO3− balance. No change in CaM expression was detected after 7days exposure to acidified seawater. This study provides insight into the molecular level changes taking place following exposure to acidified seawater in a non-calcifying, ubiquitous, organism.
Gesehen am 09.06.2017